IDEOLOGI VIRUS DALAM REVIEW IDEOLOGI DAN FILSAFAT SOSIAL - Sujarwa, Sujarwa; Handayani, Endang Sri (Universitas Ahmad Dahlan, 2020)
Reivew of the article titled The Virus of Ideology tries to understand what the author's exposure is related to the Covid-19 Pandemic event from the perspective of ideology and social philosophy. This paper tries to provide an initial description of the various forms of natural life that have occurred on earth, both natural disasters and epidemics that have occurred. In his presentation, he asserted that all things that have happened have only been responded to by humans as a disaster that has passed even though it has taken a lot of wealth, objects, and lives. Humans arrogantly discovered by new technologies feel more prepared to deal with similar things. But, in the era of the pandemic covid-19, it turned out that it couldn't do much. The era that has globalized is needed together to work together not only in one country but between countries in the world. It broke the assumption of many people or countries whose ideological beliefs were often used as fanatic shields or powerful weapons to overcome all the challenges of their nation, apparently being broken by unarmed viruses. This reminds us that human beings really need to recognize liberation - in the form of the realm of death - in order to re-express their thoughts to remember about the origin of human beings and where they will return.